KETRAMPILAN COLOUR CORRUGATED PAPER (KOKORU) TERHADAP MOTORIK HALUS ANAK AUTIS HIPOAKTIF - Cintya Taradipta, Shanaz (Jurnal Pendidikan Khusus, 2016)
ABSTRACTColor corrugated paper (Kokoru) skill was used to enhance the fine motoric skill of hypoactive autism children. The purpose of this research was to obtain the actual description of fine motoric ability of hypoactive autism children before and after giving intervention using color corrugated paper (Kokoru) skill. This research was implemented in PAUD inclusion Tunas Bangsa Blitar with 6 people as the subject and the time used in this research was 10 times meeting with 8 times intervention. The research design used was one group pre test post test design. The data collection method used was intervention and documentation. The data analysis was statistic non parametric using wilcoxon match pair test formula. The research result indicated Z counted 2.20 whereas the value of Z table in 5% significant for two sides examination (Zt = 1,96) so that Ho was refused (2.20 > 1,96). Based on the explanation it could be concluded that there was significant influence of color corrugated paper (Kokoru) skill toward fine motoric of hypoactive autism children. Keywords: Fine Motoric, Color Corrugated Paper (Kokoru)